Checklist Method in Evaluation of Collection Development - Dian Hafsera; Lailatur Rahmi; Fadhila Nurul Husna Zalmi; Ilham Kamil Harahap (Program Studi Ilmu Perpustakaan UIN Alauddin, 2022)
This study aims to identify and analyze the availability of a collection of compulsory subject teaching materials in the Library Science study program at UIN Imam Bonjol Padang. This quantitative research uses the checklist method. The research data was obtained from the RPKS/Syllabus reading list for compulsory subjects and interviews. The results of this study include an explanation of the collection based on the type of subject of the collection, the language of the collection, and the percentage of the availability of the collection to the needs of Lecturers at the Faculty of Adab and Humanities UIN Imam Bonjol. The results of this study indicate that the types of collections used in the 2018/2021 Academic Year are 75% of English Language Textbooks and Special Guidelines related to Library Science, especially in Processing Collections both Internationally and from the National Library. Data analysis shows that the number of reading lists of 20 compulsory subjects in the study program is 172 titles, with an average of 1-2 copies originating from purchases and gifts if more than 10 copies. Document data analysis resulted in the number of available reading lists in 20 courses, with the number of available collections being 37.2% and not available as much as 62.7%.